Blood and Iron: The Rise and Fall of the German Empire 1871 – 1918 - Ozgumus, Arzu Melek (Cappadocia Journal of Area Studies, 2024)
It is always very interesting to read the German history, which sheds light on a nation which has been built in less than two centuries and hit almost the top of Human Development Index. The origins of its economic and political dominance can be traced back to the beginning of the German Empire’s formation. In Blood and Iron, Katja Hoyer delves into the rise of German Empire and its eventual fall, leading to the First World War, a pivotal event that reshaped the European map. In the first chapter of the book, Hoyer covers the period between 1815-1871, beginning with the Vienna Congress in 1815, where Austria-Hungary and Prussia started their competition on the hegemony over the German states – which ultimately resolved in favor of Prussia. After defeating Napoleon, Prussia gained Rhineland and Ruhr coalfields during this period hinting at their burgeoning industrial and economic power. Although the German Confederation created at that time was led by Austria, the balance of power began to shift with the rise of Otto von Bismarck in the politics. Bismarck was a junker, landowner nobility, who became a member of the Prussian Parliament in 1847. Following his terms as Ambassador in France and Russia, he was recalled to Berlin by Wilhelm I in 1862 to support passing the military budget. This was the beginning of a relationship between Wilhelm I and Bismarck that will have a defining impact in history, a relationship Hojeremphasizes as having a profound impact on German politics. Starting from this point in the book, Hoyer frequently reminds the reader of the famous “blood and iron” speech of Bismarck, in which he emphasizes that Germany's fate would be determined through decisive military and industrial strength. This speech becomes a recurring theme in Hoyer's analysis. Bismarck’s Reich, the second chapter of the book, focuses on the years when Bismarck and Kaiser Wilhelm ruled as the Chancellor and Emperor of the German Empire respectively, from 1871 to 1888. It begins with Wilhelm, the King of Prussia, becoming the Emperor of the German Empire, and getting the title of Kaiser Wilhelm on 18 January 1871 in Versailles Place after the defeat of France in the Franco-German was of 1870-71. The chapter introduces the governmental structure of the Reich, which consisted of the Kaiser, Imperial Chancellor, the Bundesrat (the upper of parliament), and Reichstag (the parliament). Hoyer meticulously examines how Bismarck ensures the central role given to Prussia, and how he uses his power and position to create a German national identity. She explores how Bismarck implements a cultural strategy, Kulturkampf, to suppress the religious identities, especially of Catholic minorities under Protestant Prussian rule. Kulturkampf also aimed at the secularization of education and this has been a milestone in the creation of young generations with German identity. Despite resistance and the rise of pro-Catholic Centre Party (Deutsche Zentrumspartei) in politics, Hojer argues the enduring impact of this through the end of the book when discussing the First World War. In this chapter, the writer also briefly mentions the Jewish Question, as it was a significant debate around the same time. She emphasizes events like financial crisis or migration of Polish Jews taking over jobs of Germans which increased anti-Semitism. However, both Kaiser and the Chancellor viewed the Jewish issue as a matter of religion, rather than one of race. Through careful analysis, Hoyer captures the complexities of governance, cultural strategies, and social tensions during this formative period of the German Empire. In this chapter, Hoyer also underlines diplomatic skills of Bismarck. While she doesn’t mention the Concert of Europe when discussing Bismarck’s foreign policy, she clearly indicates how carefully he keeps a balance between all European powers. She criticizes him, in the following parts of the book, for building all his foreign policy around himself, which was doomed to fail after his resignation. The writer kept the third chapter of the book, Three Emperors and a Chancellor, covering the period between 1888 and 1890 notably brief, as this was a transition period. The chapter succinctly outlines key events such as the death of Kaiser Wilhelm, the brief reign of his son Freidrich III, wo passed away in just 99 days after his coronation, and the ascension of son Wilhelm II as the last Kaiser. Bismarck continues to be the Chancellor, counselling three successive emperors. However, the rising tensions and disagreements with Kaiser Wilhelm II ultimately leads to his resignation in 1890. The fourth chapter, Wilhelm’s Reich, serves as the second major segment of the book following Bismarck’s Reich. Hoyer portraits Wilhelm II as a young, ambitious, brave and visionary Emperor, unlike his grandfather’s, more modest and humbler demeanor. Due to his powerful character, Wilhelm II prefers Chancellors that he can easily control, and who can maintain a low profile in the politics. Under Wilhelm II’s leadership, he encourages further technological and industrial development, paving the way to German Empire to get a unique place in global trade with its specialization. While these developments increase the national wealth, but this was not reflected in people’s purchasing power. The working class becomes poorer, despite bankers, mostly Jews, becomes richer. The developing technology causes a decline in the need for workforce, exacerbating the challenges faced by a growing population. Developments in chemistry, resulted in new fertilizers, causes the food prices to decrease and leads the farmers into poverty, who eventually migrate to urban areas to seek jobs. Despite economic turmoil, Wilhelm II sought budget approval from the Reichstag to modernize the army. His ambitions to expand military power, however, intensified with the introduction of Weltpolitik, which was the imperialist foreign policy to make German Empire a world power. The book underlines that Wilhelm II saw Weltpolitik to bring all Germans’ together, including liberals, conservatives, social democrats, proving the power of iron in blood in German politics. Initially the writer expresses her hesitations about the character of Wilhelm II, questioning whether he was intelligent and proactive, or merely ignorant and easily influenced by a small circle of advisors. By the end of the fourth chapter, however, she clearly indicates how easily he was influenced by others, a vulnerability which ultimately leads him to take the decisions that brought his country into the First World War. In the fifth chapter, Catastrophe, Hojer summarizes the First World War and how Germany’s plans failed after the war began. Because of Weltpolitik, Great Britain, France and Russia allies against Germany, culminatinginto a war of attrition where both sides face with heavy loses. By the end of the war, Germany faced inevitable military defeat, widespread poverty among its population, with the British naval blockade worsening the situation. These aspects led to end of the war with armistice negotiations, which forced Kaiser Wilhelm II’s abdication and declaration of Germany as a republic. In the final chapter, Hoyer concludes by highlighting the flawed foundations of the German nation, “blood and iron”, and how it destroyed borders, empire and military of Germany. But she also emphasizes Bismarck’s legacy and its enduring influence, and that it will survive with the rise of defensive nationalism after the defeat in the First World War. Hoyer summarizes the history of German Empire by touching upon education, literacy, education, religion, economy and socio-cultural changes of the time. She provides a clear picture of the nation-building process that lead to small German states into Germany we know today. Details she focused on, indeed, helps the reader to understand the German society, industry and economy today. Hoyer’s book can be seen as portraying Bismarck as the person who built the German nation -and national identity-, and Wilhelm II as the one who lead to the collapse of the Empire. While this seems a plausible approach initially, the details she provides explain the context of the time. It was the time when the collapse of Ottoman Empire has started, the European powers’ competition over its territory was already risking the Concert of Europe, and there was little chance for small German states to survive without a confederation. She also emphasizes how naturally these states stick to Germany even after the First World War. In other words, while she underlines the top-down nature of policies and transformation of German nation, she also gives hints about how inevitable this change was by focusing on the industrial and economic dynamics of the time.